Efeitos da ginástica abdominal hipopressiva no tratamento da incontinência urinária de esforço de mulheres: estudo clinico - Vaz, Luciene Aparecida José (2018)
Introduction: Stress Urinary Incontinence (SUI), defined as involuntary loss of urine to exertion, coughing or sneezing, has a negative effect on women's lives. The training of pelvic floor muscles is considered gold standard in the treatment of this condition, while the literature on the use of abdominal hippopressive gymnastics (AHG) is still poor. Objectives: To verify the effects of AHG in the treatment of SUI in women; to assess the impact of AHG on the urinary loss of women with SUI; to evaluate the impact of AHG on the function of the pelvic floor muscle (PFM) of women with SUI; and to evaluate the impact of AHG on the perception of the quality of life (QoL) related to the urinary loss of women with SUI. Materials and methods: Clinical study. Sample comprised of 21 women, who obeyed the following inclusion criteria: being literate, presence of SUI proven by urodynamic study, and ability to contract PFM. Exclusion criteria were: presence of degenerative diseases, diabetes and decompensated hypertension. Participants were assessed before and after the intervention. The severity of SUI was assessed from the voiding diary, where the woman noted for seven days the urinary frequency of the day and night, the frequency of urinary loss and the exchange of absorbent. The PFM function was assessed by vaginal palpation, quantified by the Modified Oxford Scale, and contraction pressure through Peritron ™. Three sustained maximum voluntary contractions were performed for five seconds, and one minute interval between them in each method. The perception of quality of life related to urinary loss was evaluated through the International Consultation on Incontinence Questionnaire - Short Form (ICIQ-SF), Pelvic Floor Distress Inventory (PFDI-20) and Pelvic Floor Impact Questionnaire (PFIQ -7). The intervention consisted of 12 sessions divided in 6 weeks, with two weekly sessions, divided into 3 phases with progression in each phase of AHG respecting its basic principles. The data were statistically analyzed using the SPSS V20 software, using the Wilcoxon test. A significance level of 5% was adopted. Results: The mean age of the women included was 57.95 ± 13.43 years, body mass index of 26.68 ± 5.06 kg / m², 5 (24%) women with vaginal deliveries. There was no difference, after the intervention, in the severity of incontinence, as well as in the perineal function measured by vaginal palpation [2 (1-3) versus 2 (1-3), p = 0.157], however, there was an increase in the function perineal pressure measured by contraction pressure measured by manometer [16.40 cmH2O (2.10-37.70) versus 19.40 cmH2O (0.73-41.70), p = 0.004 *]. There was an improvement in the perception of quality of life related to pre and post-intervention urinary loss according to ICIQ-SF questionnaires [13.00 (3.00-2.00) versus 10.00 (0.00-19, 00), p = 0.010 *] and PFDI-20 urinary domain [41.50 (12.50-83.25) versus 29.00 (0.00-100.00), p = 0.020 *]. Conclusion: AHG did not decrease urinary loss in women with SUI, however, it increased the strength of PFM, and improved the perception of QoL related to the urinary loss of these women.